Complexidade linguística: um panorama e um estudo de caso - Leal, Ednei de Souza (Universidade Federal de São Carlos, 2020)
Language complexity is once again the object of study in Linguistics after being largely assumed as a resolved or uninteresting issue. Differently, however, from the 19th century perspective, during which linguistic complexity had already been the object of study, now its investigation is free from the prejudices that associated languages to the mental capacity of their speakers, and linguistic complexity is no longer seen today as a truism, as it transpired in the Sructuralist view until the middle of the 20th century. In the 21st century, new understandings about the language, brought by increasingly sophisticated analytic tools and by increasingly clear ideas about the typology of languages, it is finally possible to fully study language complexity, a characteristic inherent to every natural language, but that differs in its nuances and details, and is today measured by linguists who propose metrics for practically all levels traditionally investigated by Linguistic Studies, like Dahl (2004), McWhorter (2001), Culicover (2012), Kusters (2003). In this sense, this thesis proposes a panoramic look at studies on linguistic complexity from the last decade of the twentieth century to today. We propose, firstly, a non-exhaustive historiographic overview of the term “linguistic complexity” throughout the history of linguistics or studies that were inclined to deal with language. After the historical overview, we seek to show how linguistic complexity is seen today as a genuine object of linguistic studies. It is also important to mention the different techniques for measuring linguistic complexity, at the most varied levels of languages studied. Finally, we propose a brief exercise analyzing a phenomenon characteristic of Brazilian Portuguese (BP), topic constructions, with the purpose of investigating whether this phenomenon makes the language more or less complex in relation to its European variety, which seems to present the phenomenon not as often or in the same way as BP. This thesis takes as a theoretical-methodological parameter the proposals of Philosophy of Linguistics and Historiography of Linguistics, as well as the proposals already in vogue of several linguists who propose to study linguistic complexity in its most varied forms.
Language complexity: an overview and a study
Keywords: Complexidade linguística; Filosofia da Linguística; Historiografia da Linguística; Language complexity; Philosophy of Linguistics; Historiography of Linguistics; LINGUISTICA, LETRAS E ARTES::LINGUISTICA::TEORIA E ANALISE LINGUISTICA